2019
DOI: 10.1111/ene.14131
|View full text |Cite
|
Sign up to set email alerts
|

Value of insoluble PABPN1 accumulation in the diagnosis of oculopharyngeal muscular dystrophy

Abstract: Background and purpose The aim was to assess the value of insoluble PABPN1 muscle fibre nuclei accumulation in the diagnosis of atypical cases of oculopharyngeal muscular dystrophy (OPMD). Methods Muscle biopsies from a selected cohort of 423 adult patients from several Italian neuromuscular centres were analysed by immunofluorescence: 30 muscle biopsies of genetically proven OPMD, 30 biopsies from patients not affected by neuromuscular disorders, 220 from genetically undiagnosed patients presenting ptosis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…8,30 PABPN1 is essential for cell vitality playing critical roles at multiple steps in posttranscriptional regulation of gene expression and is expressed in all cells. 27 Exactly how the expanded PABPN1 causes muscle weakness in the affected muscles (such as LPS and pharyngeal muscles) is not known. 26 The involvement of Mueller’ muscle in this disease, a smooth muscle, is of interest as it has not been described by any other author in the literature to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,30 PABPN1 is essential for cell vitality playing critical roles at multiple steps in posttranscriptional regulation of gene expression and is expressed in all cells. 27 Exactly how the expanded PABPN1 causes muscle weakness in the affected muscles (such as LPS and pharyngeal muscles) is not known. 26 The involvement of Mueller’ muscle in this disease, a smooth muscle, is of interest as it has not been described by any other author in the literature to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Late changes include increased fibrous connective tissue and deposition of adipose tissue. [25][26][27] Despite the marked disappearance of the levator palpebrae superioris (LPS) muscle cells and the extensive degenerative changes, Johnson and Kuwabara reported that Mueller's smooth muscle was unaffected. 5 This has not been the author's (D.R.J.)…”
mentioning
confidence: 99%
“…A more specific finding is intranuclear tubulofilamentous aggregates of 8.5 nm outer diameter, which were observed approximately in 4% of the myonuclei by electron microscopy [39]. Of note, the detection of PABPN1-positive insoluble intranuclear aggregates was reportedly 100% sensitive and 96% specific for OPMD diagnosis [43].…”
Section: Histologymentioning
confidence: 99%
“…This disorder may mimic the clinical manifestations of the POLG-related disorders in which PEO is the predominant feature. OPMD is caused by pathogenic variants in PABPN1 and inherited in either an autosomal dominant or an autosomal recessive manner [48]. d) Amish lethal microcephaly: It is characterized by microcephaly and early death.…”
Section: C) Oculopharyngeal Muscular Dystrophy (Opmd)mentioning
confidence: 99%
“…CPEO is sometimes complicated by mild proximal muscle weakness and dysphagia, and can be considered to lie on a spectrum of disease from pure CPEO to Kearns-Sayre syndrome phenotype. Some individuals with CPEO (< 20%) have a pathogenic single-nucleotide variant of mtDNA (e.g., m.3243A>G) [48]. f) Kearns-Sayre syndrome (KSS): A mtDNA deletion syndrome, is a multisystem disorder de ined by the triad of onset before age 20 years, pigmentary retinopathy, and progressive external ophthalmoplegia (PEO).…”
Section: E) Chronic Progressive External Ophthalmoplegia (Cpeo)mentioning
confidence: 99%